The tower of Nero - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2022)
As Lester and his demigod master Meg travel to New York for Lester's final challenge in order to return to his place on Mount Olympus, they must face the Tower of Nero, Apollo's arch nemesis, Python, and Meg's stepfather.